Unity in Diversity: Respon Gereja Suara Kebenaran Injil di Kota Medan dalam Merawat Kemajemukan - Rinto Sirait (Vox Dei: Jurnal Teologi dan Pastoral, 2021)
This article aims to determine the role of the church (specifically the Voice of the Gospel Church) in caring for pluralism in Indonesia. Pluralism is a gift from God to the Indonesian people. However, pluralism in Indonesia, especially religious pluralism, has been tested. An inaccurate understanding by a group of people has given rise to intolerant actions that injure pluralism which were mutually agreed upon by the founders of the Indonesian nation. By using qualitative research methods with an exploratory study approach, this research contributes knowledge about the response of the Voice of the Bible Truth Church in Medan City in an effort to care for pluralism in Indonesia, including building inter-religious cooperation with all components of society in realizing a just and prosperous society, have an attitude of tolerance for differences in society, and the church should not be reactive to acts of intolerance; Instead, you have to show love in action. The church initiated interfaith dialogue to overcome deadlocks in religious pluralism.